Pilihan Destinasi oleh Pelancong Asing : Satu Analisa Menggunakan Teknik Proses Hirarki Analisis (PHA) - Norhaslinda, Zainal Abidin (2003)
This study was carried out to determine the attractions that influence tourists in choosing their destination(s) before starting their journey. Furthermore, this study as aims to determine the main attractions in the thee ASEAN countries namely Malaysia. Thailand and Indonesia. The data for this study were collected through personnel interview at seven locations in Peninsular Malaysia using questionnaires. A technique called Analytical Hierarchy Process (AHP) was used. AHP is a tool in Multiple Criteria Decision Making in the field of Operational Research (OR). In this study, AHP analyses the data using pairwise comparison to find out the preferences for six attraction factors attraction. This study shows that ‘safety’ is the most important factorr in influencing the selection of tourism destination(s). This is followed by ‘value for money’ beautiful beaches and the availability of facilities for sea-sport, ‘cultural and historical sites’. ‘nightlife and entertainnient‘ and finally ‘adventure and wilderness‘. This analysis shows that Thailand is Malaysia‘s closest competitor and is the most favourite destination by the long-haul tourists. Meanwhile, this study also shows that Malaysia have the potential to be more successful due to it being the main destination chosen by the various types of respondents based on the six factors.